Associations between sex, age and spiritual well‐being scores on the EORTC QLQ‐SWB32 for patients receiving palliative care for cancer: A further analysis of data from an international validation study. (21st August 2019) - Rohde, Gudrun Elin; Young, Teresa; Winstanley, Julie; Arraras, Juan I.; Black, Kath; Boyle, Fran; Bredart, Anne; Costantini, Anna; Guo, Jingbo; Irarrazaval, Maria E.; Kobayashi, Kunihiko; Kruizinga, Renske; et al.
Abstract: Objective: The EORTC QOL Group has recently completed the cross‐cultural development and validation of a standalone measure of spiritual well‐being (SWB) for cancer patients receiving palliative care: the EORTC QLQ‐SWB32. The measure includes four scales: Relationships with Others, Relationship with Self, Relationship with Someone or Something Greater, and Existential, plus a Global‐SWB item. This paper reports on further research investigating relationships between sex, age and SWB for patients receiving palliative care for cancer—adjusting for other socio‐demographic, clinical and function variables, including WHO performance status and EORTC QLQ‐C15‐PAL emotional and physical function scores. Methods: Cross‐sectional data from the validation study were used, and chi‐square, independent t tests, Mann–Whitney U tests and multiple regression analyses applied. Results: The study included 451 participants with advanced and incurable cancer, from 14 countries. Adjusted analyses found better scores for female participants than males on three of the four EORTC QLQ‐SWB32 subscales; Relationship with others, Relationship with Someone or Something Greater and Existential plus Global‐SWB. Older age was positively associated with better Relationship with Self. Conclusion: The findings from our participants suggest that it might be beneficial if healthcare providers seeking to address patients' spiritual needs pay particular attention to male patients, younger patients and those with poor emotional functioning.